Seasonal variation in crop yield and reduction of phytic acid content through soaking and germination of kodo millet (Paspalum scrobiculatum L.) germplasm - Suneetha, C.; Sukumar, M. (National Science Foundation: Colombo, 2026)
Kodo millet (Paspalum scrobiculatum L.) is a nutrient-rich, gluten-free grain with significant potential for enhancing food security. However, its high phytic acid content limits mineral bioavailability, necessitating strategies for reduction. This study evaluated 75 kodo millet germplasms sourced from ICRISAT and cultivated under surface drip irrigation during the 2022-2023 Rabi (dry/winter season) and 2023-2024 Kharif (wet/monsoon season) at the University of Hyderabad. Two-way ANOVA was used to identify IPs 69 as the highest-yielding variety across both seasons, while IPs 240 (Kharif) and IPs 236 (Rabi) were the lowest yielding. Seasonal variations influenced overall productivity, with Rabi conditions favouring grain production. Phytic acid levels were analysed in husked and dehusked grains, showing significant genetic variation but minimal seasonal influence on post-harvest dehusking. To enhance mineral bioavailability, response surface methodology (RSM) was used to optimize soaking (20.63 h, 38.49 °C, pH 4.08) and germination (36.29 h, 27.29 °C, 65.18% moisture) conditions. Soaking alone resulted in a substantial reduction of phytic acid by 48.11%, while soaking followed by germination led to a total reduction of 53.97%, indicating that germination contributed only a marginal additional decrease beyond soaking. These findings demonstrate that soaking is the primary contributor to phytic acid degradation, with germination playing a supplementary role. This study highlights the importance of selecting high yielding, nutritionally superior kodo millet varieties while optimizing post-harvest treatments to improve their dietary value. The findings underscore the role of genetic diversity, environmental conditions, and processing interventions in determining the grain’s nutritional and agronomic potential. Future research should focus on integrating advanced breeding strategies and optimized processing methods to enhance the bioavailability of essential micronutrients, ensuring kodo millet’s broader adoption in sustainable food systems.
Keywords: Kodo millet flour; Micro nutrient bioavailability; Millet germplasms; Paspalum scrobiculatum L.; Phytic acid